Pengaruh Motivation dan Employee Performance terhadap Public Service Di Kecamatan Cisaat Kabupaten Sukabumi - Ryan Kurniawan; Muhammad Rezzy Rizaldhi (Cakrawala Repositori IMWI, 2020)
This study aims to determine: (1) the relationship and influence of motivation on public service, (2) the relationship and influence of employee performance on public service, and (3) the relationship and influence of motivation and employee performance simultaneously on public service. The subjects of this research are all employees of Cisaat District, Sukabumi District, totaling 31 people. Methods of data collection through survey by using questionnaire. Data analysis technique used in this research is Multiple Linear Regression Analysis. The results showed that: (1) the motivation positively affect the public service; (2) the employee performance has no effect on public service; (3) simultaneously motivation and employee performance postively affect the public service.